Reappraisal of quality indicators in the blood center of a tertiary care teaching hospital - Are we ready for accreditation? - Gargi Mukherjee; Parijat Pramanik; Dipmala Das; Asitava Deb Roy (Global Journal of Transfusion Medicine, 2021)
Background and Objectives: Ensuring quality in transfusion services has become an essential part of the hospital quality management system to provide safe blood supply to the patients. To assess the overall quality performance of our blood center, this study was conducted to evaluate the five mandatory quality indicators (QI) put forward by the National Accreditation Board for Hospitals and Healthcare Providers (NABH) and make recommendations, if any, for improvement of the same. Methods: The five mandatory QIs (defined by NABH) were observed and monitored monthly for a period of 1 year from April 2019 to March 2020, information was gathered in a structured manner, root causes for any deviation were analyzed, and specific corrective and preventive actions were taken. Results: The overall performance was found to be satisfactory with the mean transfusion-transmitted infection % being 1.82%, mean transfusion reaction rate 0.30%, and mean wastage rate 13.5%. The turnaround time was maintained at 28.5 min for emergency cases and 141.38 min for routine. There was no case of component quality control failure during the study period. Conclusion: The study observed that by strictly following the quality parameters put forward by NABH, processes can be controlled in a manner that errors are avoided or kept at minimum. This, in turn, shall help in attaining higher levels of performance. The study concluded by putting forward few important recommendations.